Carlos Vergara: deslocamentos do visível - Santini, Renata Favarin (2010)
The present work is a monographic study about the visual poetic of the artist Carlos Vergara, in which I propose an approach to his process of creation. To do this, I adopt three works at the exhibition Sacred Heart - San Miguel Mission, from December 23, 2008 to March 15, 2009 at the Art Museum of Rio Grande do Sul Ado Malagoli, in Porto Alegre, RS. The aforementioned works are: St. Michael - Sacred Heart (Monotype and paint on raw canvas), SM 4 (3D lenticular) and San Miguel - Floor VI (Monotype on raw canvas). In addition, two issues influenced the development of this research: the physical displacement and the subsequent appropriation of space by the artist in his creative process. Thus, the problem proposed in this research is: How is the displacement of the visible / invisible in the work of Carlos Vergara? That is, as the physical displacement of the artist - the action of visiting certain places - and the possible shifts contained in his poetry, a sign / signs / signals from these places, relating to both in their process of creation. The work is divided into three chapters, with the first chapter deals with the person Vergara, in which the focus is the direction taken by the artist and his influences. The second chapter provides a chronological overview of the artist from the 1960s to its current production, which demarcated their production in the context of contemporary Brazilian art. Finally in the third chapter, in house procedures adopted by the artist in the preparation of the artwork from the works already mentioned, which emphasizes the concept of displacement, incorporating how the artist perceives the issue. The approach to the creative process led to confirmation of existing dislocations, confirming its nature of mobility, but also the possible variables of the visible, these issues often addressed in the production and reflection of contemporary art.